A novel electrochemiluminescence aptasensor based CdTe QDs@NH2-MIL-88(Fe) for signal amplification. (10th September 2020) - Chen, Peipei; Liu, Zhen; Liu, Jianhui; Liu, Hanbiao; Bian, Weiwei; Tian, Dong; Xia, Fangquan; Zhou, Changli
Abstract: In this work, the Fe-based metal-organic framework, NH2 -MIL-88(Fe), was used as the nanocarrier and signal enhancer for the enhancement of CdTe QDs-S2 O8 2− system, an ultrasensitive electrochemiluminescence (ECL) aptasensor was constructed for the detection of malathion. NH2 -MIL-88(Fe) can immobilize abundant CdTe QDs on the interior framework and outer surface. Meanwhile, the mechanism of drastically increasing the ECL intensity of CdTe QDs has been established. Firstly, Fe(II) from NH2 -MIL-88(Fe) as the signal enhancer, could react with S2 O8 2− to generate Fe(III) and SO4 － . Then, the Fe(III) can be reduced under the electrochemical reaction. Thus, the cycle-type reaction was come true to produce amounts of SO4 －, which could react with CdTe QDs to realize a relative stronger ECL signal. As a result, CdTe QDs@NH2 -MIL-88(Fe) derived novel ECL aptasensor for malathion detection displayed superior sensitivity, with a linear range from 1.0 × 10 −6 to 1.0 μg L −1 and the detection limit was 0.3 pg L −1 . Importantly, NH2 -MIL-88(Fe) as the nanocarrier and signal enhancer has provided a direction for ultrasensitive target analysis.